Contar la violencia : influencia del turismo en la narración de episodios violentos en el área maya ixil (Guatemala) - Coralie Morand (Études Caribéennes)
From 1960 to 1996, Guatemala experienced a particularly brutal internal armed conflict, leaving a lasting rift in society over the real nature of the conflict. In the early 1980s, the state-led counter-insurgency took on genocidal overtones in several parts of the country, particularly in the mayan ixil zone in the north of El Quiché department. Nestling in the heart of the Cuchumatanes mountain range, this region attracts a small number of trekking and memorial tourists, leading to the development of initiatives aimed at passing on the memory of the conflict to these special visitors. Based on an eleven-month ethnographic field study, this article analyses how the experience of violence is put into language, depending on the context in which it is expressed. The author sets out to understand the way in which the presence of tourists in the area influences what is said about violence and how women members of an artisanal cooperative relate their memories of violent episodes.